Desenvolvimento de protótipo de dashboard para sistema de medição de desempenho do processo de compras - Gushiken, Stephany Rie Yamamoto (Universidade Federal de São Carlos, 2026)
This research addresses performance measurement in the purchasing process of multinational companies, focusing on the use of dashboards as a decision-making support tool. The study aims to develop a prototype dashboard for the purchasing process capable of meeting the informational needs of decision-makers at the operational, tactical, and strategic levels. To achieve this objective, a quantitative approach and the Design Science Research method were adopted, guiding the development of the dashboard prototype so that it is applicable to the organizational reality of the analysis unit, a multinational company in the cutting and welding segment. The literature review analyzes the themes of performance measurement, the purchasing function in the supply chain, and the relationship between performance measurement in purchasing and the use of dashboards, understanding the needs of different purchasing decision-makers. As main results of the literature review, 68 indicators applicable to the purchasing process were identified, as well as literature that supported the prioritization of these indicators considering key characteristics and, subsequently, their classification at the operational, tactical, and strategic levels. Data collection involved mapping tables in the ERP (Enterprise Resource Planning) system of the analysis unit, SQL (Structured Query Language) queries, and DAX calculations in Power BI. The developed prototype increased information transparency, promoting decisions such as direct interaction with suppliers to mitigate supply risks, developing new suppliers, or even prioritizing resources based on financial results guided by data related to the purchasing process and extracted directly from the analysis unit's ERP system. The research demonstrates that well-structured dashboards tailored to user needs improve the organization's decision-making process, enabling the migration from a reactive and manual management model to a proactive and data-driven approach, fundamental for competitiveness in global supply chains. For future studies, it is recommended to increase the concentration of data in the ERP and create impartial evaluation checklists when the researcher is immersed in the analysis unit.
Development of dashboard prototype for purchasing process performance measurement system
Keywords: Compras; Purchasing; Dashboard; Sistema de medição de desempenho; Indicadores de desempenho; Performance measurement system; Performance indicators; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; 9. Indústria, Inovação e Infraestrutura